Musculoskeletal imaging : a core review - Paul J. Spicer; Francesca Beaman; Gustav A. Blomquist; Justin Montgomery; Matthew E. Maxwell (Philadelphia : Wolters Kluwer, 2021)
Prepare for success on the musculoskeletal imaging component of the radiology Core Exam! Musculoskeletal Imaging: A Core Review, Second Edition, is an up-to-date, practical review tool written specifically for the Core Exam. This helpful resource contains 300 image-rich, multiple-choice questions with detailed explanations of right and wrong answers, fully revised content, high-yield tables for easy review, and additional eBook questions to ensure you$1 (Bre ready for the Core Exam or recertification exam.s
Keywords: Diagnostic imaging Examinations, questions, etc; Musculoskeletal system Wounds and injuries Examinations, questions, etc; Musculoskeletal system Imaging Examinations, questions, etc